Mechanics of materials - Pytel, Andrew (Thomson, 2003)
This introductory textbook covers stress, strain, torsion, columns, inelastic action and topics specific to the use of beams. These include shear and moment in beams, stresses in beams, deflection of beams, statically indeterminate beams, and composite beams. Diagrams and other illustrations are prominently featured. Approximately 30 pages of useful tables are provided. The authors teach at the Pennsylvanian State University. Annotation c. Book News, Inc., Portland, OR (booknews.com).